Effectiveness of Insulin Analogs Compared with Human Insulins in Pregnant Women with Diabetes Mellitus: Systematic Review and Meta-analysis - Leyna Leite Santos; Jamilly Leite Santos; Luciano Timbó Barbosa; Ivan do Nascimento da Silva; Célio Fernando de Sousa-Rodrigues; Fabiano Timbó Barbosa
Abstract Diabetes during pregnancy has been linked to unfavorable maternal-fetal outcomes. Human insulins are the first drug of choice because of the proven safety in their use. However, there are still questions about the use of insulin analogs during pregnancy. The objective of the present study was to determine the effectiveness of insulin analogs compared withhuman insulin in the treatment of pregnant women with diabetes througha systematic review withmeta-analysis. The search comprised the period since the inception of each database until July 2017, and the following databases were used:MEDLINE, CINAHL, EMBASE, ISIWeb of Science, LILACS, Scopus, SIGLE andGoogle Scholar.We have selected 29 original articles: 11 were randomized clinical trials and 18 were observational studies.We have explored data from 6,382 participants. All of the articles were classified as having an intermediate to high risk of bias. The variable that showed favorable results for the use of insulin analogs was gestational age, with a mean difference of - 0.26 (95 % confidence interval [CI]: 0.03-0.49; p = 0.02), but with significant heterogeneity (Higgins test [I2] = 38%; chi-squared test [χ2] = 16.24; degree of freedom [DF] = 10; p = 0.09). This result, in the clinical practice, does not compromise the fetal well-being, since all babies were born at term. There was publication bias in the gestational age and neonatal weight variables. To date, the evidence analyzed has a moderate-to-high risk of bias and does not allow the conclusion that insulin analogs are more effective when compared with human insulin to treat diabetic pregnant women.